2014
DOI: 10.1111/inm.12061
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic engagement between consumers in suicidal crisis and mental health nurses

Abstract: Registered nurses within public mental health services play crucial roles in helping people recover from suicidal crisis. However, there is a lack of understanding of how care is experienced in this context, and available evidence suggests that nurses and consumers are often dissatisfied with the quality of care. There is thus an imperative to generate understanding of needs and experiences of both groups with a view to informing practice development. This article summarizes qualitative findings from a multime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
124
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(127 citation statements)
references
References 48 publications
2
124
0
1
Order By: Relevance
“…However, psychiatry continues to be heavily influenced by a biomedical ideology that in turn affects how mental health workers understand suicidality and approach suicidal patients (Hagen et al, 2017; Michel et al, 2002). In keeping with previous research (Lees et al, 2014; Talseth et al, 1999, 2001), our study suggests that suicidal patients want mental health workers to focus less on medical models and approaches in their care for them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, psychiatry continues to be heavily influenced by a biomedical ideology that in turn affects how mental health workers understand suicidality and approach suicidal patients (Hagen et al, 2017; Michel et al, 2002). In keeping with previous research (Lees et al, 2014; Talseth et al, 1999, 2001), our study suggests that suicidal patients want mental health workers to focus less on medical models and approaches in their care for them.…”
Section: Discussionsupporting
confidence: 90%
“…Although the guidelines have raised mental health workers’ awareness about suicidality, the main emphasis is on the assessment and management of suicide risk and not on how to provide good care to suicidal patients. Previous research has shown that patients appreciate being cared for by empathic health workers who value them as individuals and respond to their needs (Berg, Rørtveit, & Aase, 2017; Lees, Procter, & Fassett, 2014; Sun, Long, Boore, & Tsao, 2005; Talseth, Jacobsson, & Norberg, 2001; Talseth, Lindseth, Jacobsson, & Norberg, 1999; Vatne & Nåden, 2014) and who inspire hope and move them from a ‘death-oriented’ position to a ‘life-oriented’ position (Cutcliffe & Stevenson, 2007; Cutcliffe, Stevenson, Jackson, & Smith, 2006). Berg et al’s (2017) review shows that, for suicidal inpatients, safety means ‘feeling safe’, which involves establishing close connections with the professionals, being protected by supportive staff and re-establishing a sense of control over their lives.…”
Section: Introductionmentioning
confidence: 99%
“…Analysed using thematic analysis inspired by Braun and Clarke. Gadamerian hermeneutic approach.• Connectedness, someone who cares• Hospital admission important for staying alive• Support from family and friendsLees, Procter and Fassett, 2014 [26]. AustraliaTo explore the experiences and needs of mental health-care consumers who had a suicidal crisis (shortened).Nine patients recovered from a recent suicidal crisis where they received mental health in-patient care.Setting not specified.…”
Section: Resultsmentioning
confidence: 99%
“…The sample of suicidal patients included in this review reported multiple and diverse causes of their suicidal crises [26, 27], but all patients experienced feelings of overwhelming suffering and increased vulnerability [2731]. Patients experienced increased emotional sensitivity regarding how they were perceived and approached by health care professionals, and this sensitivity affected their perceptions of themselves, their recent suicide attempt, their therapeutic relationships [26, 32, 33] and their feelings of safety in the hospital [31, 34, 35]. Patients’ connections with health care professionals enabled them to feel valued as human beings by meeting someone who cares ; to feel understood by receiving a confirmation of feelings; and to feel respected and trusted by being acknowledged as a human being.…”
Section: Resultsmentioning
confidence: 99%
“…Many different national researchers believe they should identify sources of support for participants (Swain, Heyman, & Gillman, 1998), especially if the research involves vulnerable groups (Jewkes, Watts, Abrahams, Penn-Kekana, & García-Moreno, 2000) and sensitive topics (Lees, Procter, & Fassett, 2014).…”
Section: Tertiary Ethical Proceduresmentioning
confidence: 99%